JEJAK EMOSI DALAM GARIS DAN WARNA: STUDI ESTETIKA DAN PSIKOLOGI KARYA ANAK KELAS 4 SD N 1 SEKARAN - Izzah Syifa Ulfana; Gunadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children's paintings serve as a medium of visual expression that reflects not only aesthetic abilities but also psychological development. This study aims to describe aesthetic characteristics, reveal psychological dimensions, and analyze the relationship between aesthetic and psychological aspects in the paintings of fourth-grade students at SDN 1 Sekaran, drawing upon Viktor Lowenfeld's theory of artistic development. A descriptive qualitative approach utilizing a case study method was employed. Data were gathered through observations of art lessons, interviews with teachers and students, and documentation of the students' artwork. From the 25 pieces produced, nine were purposively selected for analysis, representing high, medium, and basic categories. The analysis examined aesthetic elements—such as line, color, shape, and composition—and the psychological dimensions reflected in each work, based on Lowenfeld's theory. The results indicate that works in the high category exhibit a more structured and harmonious organization of visual elements; the medium category shows developing visual capabilities with some simplification of forms; and the basic category displays simple visual organization while still reflecting expressive ability. Psychologically, the artworks reflect the students' experiences, imagination, interests, and emotional responses to their surroundings. The findings demonstrate that aesthetic elements and psychological dimensions are interconnected in the creation of children's art; thus, these paintings can be understood as representations of aesthetic, cognitive, and psychological development progressing in stages, consistent with Viktor Lowenfeld's theory.